β-Diversity, Community Assembly, and Ecosystem Functioning - Mori, Akira S.; Isbell, Forest; Seidl, Rupert (Trends in ecology & evolution (Amsterdam), 2018)
Evidence is increasing for positive effects of α-diversity on ecosystem functioning. We highlight here the crucial role of β-diversity – a hitherto underexplored facet of biodiversity – for a better process-level understanding of biodiversity change and its consequences for ecosystems. A focus on β-diversity has the potential to improve predictions of natural and anthropogenic influences on diversity and ecosystem functioning. However, linking the causes and consequences of biodiversity change is complex because species assemblages in nature are shaped by many factors simultaneously, including disturbance, environmental heterogeneity, deterministic niche factors, and stochasticity. Because variability and change are ubiquitous in ecosystems, acknowledging these inherent properties of nature is an essential step for further advancing scientific knowledge of biodiversity–ecosystem functioning in theory and practice. A rich body of evidence shows how biodiversity can help to sustain pools and fluxes of matter and energy in ecosystems. Understanding such diversity effects on ecosystem functioning is crucial to predicting the potential consequences of biodiversity loss. Although α-diversity has received great attention in the literature, there is a serious knowledge gap for the roles and functions of β-diversity. β-Diversity provides insights into the mechanisms driving biodiversity changes and their consequences for multiple ecosystem functions. Focusing on β-diversity is especially important in ecological communities that are subject to large environmental fluctuations and disturbances. Considering the increasing importance of variability in ecological systems, particularly in the context of global change, insights gained from studying β-diversity are of importance for both theoretical and applied ecology.